EFEKTIVITAS PROGRAM EDUKASI ONLINE PERSONAL HYGIENE MENGGUNAKAN LAGU TERHADAP PENGETAHUAN PERSONAL HYGIENE ANAK USIA SEKOLAH - Wulan Suci Ramadhani; Yufitriana Amir; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
School-age children will pass stage of growth getting more independent in personal hygiene. This study aims to find out the effectiveness of online personal hygiene education programs using song on school-age children knowledge. The design was quasy experimental with total of sample 50 and consecutive sampling technique. The univariat analysis showed majority respondents at 10 ages 31 students(62%),24 at grade 4(48%), majority pretest got same point in sufficient and less category 18 students(36%), and posttest in good knowledge 32 students(64%). The bivariat analysis with Wilcoxon alternative test shown p value (0,000), the online program personal hygiene with song effective on school-age children knowledge. Online personal hygiene song education programs is effective to school-age children knowledge. The results of this study are expected to improve students’ personal hygiene knowledge.Keywords: education program with song, knowledge, personal hygiene, school-age children